Late opening of the infarct related artery: an open or shut case?. Issue 5 (14th April 2005) - Yousef, Z R; Marber, M S; Redwood, S R
Abstract : Is there a place for the late opening of infarct related arteries, beyond the time window for myocardial salvage?